2007
DOI: 10.1111/j.1365-2929.2006.02693.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving diagnostic capabilities of medical students via application of cognitive sciences-derived learning principles

Abstract: The ability to perform differential diagnosis is enhanced by training based upon principles of cognitive sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Contemporary medical education has yet to create a codified, evidencebased approach to training to or assessing the diagnostic capabilities of medical students, residents or practitioners. These findings, in conjunction with those emerging from other DPT-oriented research [4,5,19,23] suggest that a DPT framework could contribute to the development of a codified approach to diagnostic training and assessment. It is extremely difficult for researchers to draw direct inferences regarding the cognitive factors enabling the development and improvement of diagnostic capabilities.…”
Section: Discussionsupporting
confidence: 56%
“…Contemporary medical education has yet to create a codified, evidencebased approach to training to or assessing the diagnostic capabilities of medical students, residents or practitioners. These findings, in conjunction with those emerging from other DPT-oriented research [4,5,19,23] suggest that a DPT framework could contribute to the development of a codified approach to diagnostic training and assessment. It is extremely difficult for researchers to draw direct inferences regarding the cognitive factors enabling the development and improvement of diagnostic capabilities.…”
Section: Discussionsupporting
confidence: 56%
“…The other study compared a carefully-planned IBL intervention with a long-established lecture, and found improved knowledge outcomes for the IBL group despite similar time learning. (Papa et al 2007). …”
Section: Comparisons Of Internet With Non-internet Interventionsmentioning
confidence: 99%
“…The correlation between time and knowledge outcomes confirms this observation. Isolated examples demonstrate improvements in learning efficiency through dramatically innovative instructional designs, as evidenced by learning gains despite reduction in time (Bell et al 2000;Cook et al 2005) or fixed time (Papa et al 2007), and time savings with minimal change in learning outcomes (Cook et al 2008a). However, subsequent changes to further enhance learning appear to require more time (compare, for example, Cook et al 2005 and.…”
Section: Implications: Instructional Designmentioning
confidence: 99%
“…Research at UNTHSC/TCOM involving computer-based, dual processing theory-driven approaches to DD training has demonstrated that first-and secondyear students and practicing physicians achieve improved DD accuracy. [14][15][16] Two additional semesters of AME coursework and II processing mechanisms involving pattern recognition and rule-based constructs) during case-based practice opportunities conducted in a small group, faculty-facilitated learning environment. The AME faculty now have the opportunity and challenge to organize and produce institutional review board-approved research protocols to determine whether these innovations are leading to improved DD performance.…”
Section: Resultsmentioning
confidence: 99%